Peningkatan Kualitas Pembelajaran Pendidikan Kewarganegaraan Melalui Model Pembelajaran Berbasis Portofolio di MTsN-2 Palangka Raya - Asmawati, Asmawati (Jurnal Studi Agama dan Masyarakat, 2010)
This study aimed to describe how to apply the portfolio as a learning model, and how portfolio models can improve the quality of teaching Civics Education in MTsN-2 Palangka Raya. This research is a class action. The object of this research is the learning process by using portfolio model, and the research subjects are teachers and students who are applying the model. The data are collected using observation, interviews, and documentation. Data analysis was performed since the data collection, it uses an interactive method that consists of 3 steps: 1) data reduction, 2) data display, and 3) withdrawing conclusion. Time used for this research is 4 (four) months. This reseach revealed that portfolios as a learning model can improve the quality of learning. It can be seen from the increased activity of the students in asking and answering questions, as well as increasing the quality of students in conducting group discussions